PENDEKATAN DAN ANALISIS KRITIS TARIKAN BUDAYA PRAGMATISME PENDIDIKAN ISLAM PADA DUNIA MODERN - mila, milatul fatkhiyah (Al-Miskawaih, 2024)
This article is based on the fact that educational innovation in Indonesia is still low, as reflected in the weak competitiveness of Indonesian human resources compared to other Southeast Asian countries.The emergence of pragmatism theory is expected to serve as a theoretical alternative for the approach to Islamic education innovation.This article aims to formulate the design and process of Islamic Education innovation based on qualitative research and literature study.This article is a philosophical study aimed at constructing the process of innovation in Islamic Education from the perspective of Islamic philosophy and pragmatism. It also provides solutions to the culture of educational pragmatism among academics, where all aspects of education contain elements of pragmatism, whether from educators, students, curriculum, management, or even facilities and infrastructure, concluding that the process of innovation is inevitable.In the Islamic perspective, sound faith is the key and the first step in discovering the purity of Islamic education innovation.Meanwhile, pragmatism offers a process of innovation in Islamic education based on systematic steps that begin with reflective criticism, diagnosis, inventory, contemplation, hypothesis testing, public analysis, and finally implementation.then in the pragmatization of education, it is necessary to develop the theoretical aspects that provide ethical and normative foundations, while the practical aspects can prepare professionals according to the needs of society.The proportionalization of theoretical and practical aspects is important, so that education does not give rise to hidden materialism when it overly emphasizes the practical.Keyword: Approach, Pragmatism Culture, Islamic Education.